Financial Inclusion on Creative Industry Performance: Evidence from Indonesia - Julita, Julita; Nainggolan, Edisah Putra (AIBPM Publisher, 2023)
This study aims to determine the performance of creative industries in Indonesia influenced by digital marketing and financial technology. This study also looks at the role of financial inclusion in mediating the influence of these two variables. This study uses an explanatory research approach. The sample of this research is 100 creative industry players in Indonesia. The sampling technique used is the purposive sampling method. The data analysis used is a Partial Least Square analysis. Based on the results of the discussion, it can be concluded that Digital Marketing has a significant effect on the Creative Industry. Financial Technology has a significant effect on the Creative Industry. Furthermore, the results of the study found that Financial Inclusion mediates the influence of Digital Marketing on the Creative Industry. Furthermore, the results of the study conclude that Financial Inclusion mediates the influence of Financial Technology on the Creative Industry.